Prevalence and associated factors of depressive and anxiety symptoms during pregnancy: A population based study in rural Bangladesh - Kabir Zarina N; Nasreen Hashima E; Forsell Yvonne; Edhborg Maigun (BMC, 2011)
Abstract Background Few studies have examined the associated factors of antepartum depressive and anxiety symptoms (ADS and AAS) in low-income countries, yet the World Health Organization identifies depressive disorders as the second leading cause of global disease burden by 2020. There is a paucity of research on mental disorders and their predictors among pregnant women in Bangladesh. This study aims to estimate the prevalence of depressive and anxiety symptoms and explore the associated factors in a cross-section of rural Bangladeshi pregnant women. Methods The study used cross-sectional data originating from a rural community-based prospective cohort study of 720 randomly selected women in their third trimester of pregnancy from a district of Bangladesh. The validated Bangla version of the Edinburgh Postnatal Depression Scale was used to measure ADS, and a trait anxiety inventory to assess general anxiety symptoms. Background information was collected using a structured questionnaire at the respondents' homes. Results Prevalence of ADS was 18% and AAS 29%. Women's literacy (OR 0.59, 95% CI 0.37-0.95), poor partner relationship (OR 2.23, 95% CI 3.37-3.62), forced sex (OR 1.95, 95% CI 1.01-3.75), physical violence by spouse (OR 1.69, 95% CI 1.02-2.80), and previous depression (OR 4.62 95% CI 2.72-7.85) were found to be associated with ADS. The associated factors of AAS were illiteracy, poor household economy, lack of practical support, physical partner violence, violence during pregnancy, and interaction between poor household economy and poor partner relationship. Conclusion Depressive and anxiety symptoms are found to occur commonly during pregnancy in Bangladesh, drawing attention to a need to screen for depression and anxiety during antenatal care. Policies aimed at encouraging practical support during pregnancy, reducing gender-based violence, supporting women with poor partner relationships, and identifying previous depression may ameliorate the potentially harmful consequences of antepartum depression and anxiety for the women and their family, particularly children.